Developing animal science and veterinary science students’ communication skills using a multimodal brochure assignment - Harvey, Arlene; Drury, Helen; White, Peter (Journal of Academic Language and Learning, 2020)
This paper describes a multimodal brochure assignment in an undergraduate animal science subject with a mixed cohort of animal science and veterinary science students. The assignment involved group work and peer feedback that allowed students to improve their brochures prior to submission. Support for the communication aspects of the assignment was developed by a teaching team consisting of the subject lecturer and two lecturers with a specialisation in academic language and learning. This support consisted of a rubric containing detailed communication rows, and annotated brochures illustrating written and visual features of this unfamiliar assignment genre. At the end of the subject, students were surveyed to seek their feedback on the usefulness of the assignment, the rubric (especially the detailed communication rows), the annotated brochures, and the peer review process. Results were highly positive, with students seeing value in this type of assignment for developing their communication skills. Students reported benefits in both giving and receiving (and using) peer feedback to improve their brochures. While giving feedback was considered to be helpful for enhancing both communication and understanding of the rubric, receiving feedback was mostly seen as beneficial for the purposes of editing and proofreading. Students reported that the main challenges of the assignment were in being concise and tailoring the language of the brochure to the target audience. The results suggest that while the support was viewed as very helpful, students may need more explicit and scaffolded guidance in tailoring their communication for a non-academic audience in a multimodal genre.